KEMAMPUAN GURU PAI PPG DALJAB DALAM MERANCANG SOAL HOTS PILIHAN GANDA - Realita (FITRAH: International Islamic Education Journal, 2022)
Composing questions based on HOTS (Higher Order Thinking Skill) is one of the competencies that must be possessed by teachers in the 21st century, especially teachers who have been trained in the Professional Teacher Program (PPG Daljab). This paper aims to measure the competence of Islamic Education (PAI) teachers who were in in-service training program (PPG Daljab 2021) in designing HOTS-based multiple choice questions. This is a descriptive quantitative research. The data was collected by analyzing multiple choice questions made by PAI PPG teachers. The questions were analyzed using the percentage formula. The subject of this research was the teacher of PAI PPG Daljab 2021 at the Islamic University of Ar-Raniry session 2, totaling 12 teachers. The results of the study revealed that the ability of PAI PPG Daljab teachers 2021 in designing HOTS- based questions was in the good category with a score of 58%.